Education and clinical pharmacist-led management strategies for the risk and prophylaxis of venous thromboembolism in general surgery - Zeynep Karaburç Kiracı; Nadir Yalçın; Ömer Cennet; Kutay Demirkan; Kaya Yorgancı (Thrombosis Journal, 2023)
Abstract Background Despite the risks of venous thromboembolism (VTE) in surgical patients are well defined, primary thromboprophylaxis (TP) can be neglected. The aim of this study was to evaluate the risk of VTE and appropriateness of TP and to assess the effects of education and clinical pharmacy (CP) services. Methods This study was conducted in a total of 3 periods (n = 800): pre-education (n = 340), post-education (n = 269) and CP intervention period (n = 191) and the risk of VTE and the appropriateness of TP were evaluated. At the end of pre-education period, patients were re-evaluated after education was given about the guidelines on TP and an educative poster was posted in the services (post-education period). During the CP intervention period, the CP made recommendations in terms of optimal TP use to the physicians in charge. Results While there was no significant difference in the optimal TP rate administered to the patients before and after education (138/340, 40.6% vs. 122/269, 45.4%; p = 0.238); this rate was increased to 113/191 (59.2%) in the CP intervention period (p = 0.004). High-risk patients who received one type of TP constituted the majority of patients who did not receive optimal TP. While the ratio of high-risk patients undergoing a single type of TP in the pre- and post-education periods (104/340, 30.6% vs. 83/269, 30.9%), was similar (p = 0.819); with the CP interventions, this rate was reduced to 35/191 (18.3%) (p = 0.001). Conclusion Even though education has positive influence on surgeons, the implementation of CP practices is more effective especially in terms of maintaining optimal TP.